Estudio de prefactibilidad para la instalación de una planta productora de crema facial a base de resveratrol - Maravi Jondee, Michael Jesus (2023)
The present pre-feasibility study aims to determine the market, technical and economic-financial viability for the installation of a resveratrol-based facial cream production plant. In Chapter I, the general and specific objectives will be established, the technical, economic and social justification will be made and a working hypothesis will be elaborated that will serve as the basis for the development of the project study. In Chapter II, a market study will be carried out to define the target market for the facial cream that meets the needs identified in the customers and thus calculate the demand for the project, which for the year 2026 is 46 550 units. In Chapter III, the location of the plant will be determined according to the most relevant macro-location and micro-location factors. In Chapter IV, the optimal size for the production plant will be determined considering certain aspects that have great influence on the project. In Chapter V, the production process that will be carried out will be developed, calculating the number of machines and operators necessary, in addition, the requirements for inputs and raw materials will be specified to comply with the production plan. Within this framework, the minimum areas required for each area of the production plant will be detailed and a correct plant layout will be analyzed. In Chapter VI, the administrative organization that will ensure compliance with the objectives and goals of the company will be detailed. In Chapter VII, the economic and financial aspects of the project will be evaluated to determine its viability and, finally, in Chapter VIII a social evaluation will be carried out to identify the impact that the project will have on society.